Potential Anti-SARS-CoV-2 Molecular Strategies - Roviello, Giovanni N.; Vicidomini, Caterina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Herein we describe some molecular aspects of the recent anti-COVID-19 research, including some approaches making use of natural remedies, especially from medicinal plants, in silico methods, and different experimental procedures that led to the discovery of novel targets of SARS-CoV-2 and consequently novel potential COVID-19 therapeutics. COVID-19 vaccines also find mention in this book with also a description of some adverse effects reported in some cases. Considering that the different beta coronaviruses present certain conserved biomolecular mechanisms and, thus, some common therapeutic targets, finding effective therapies for a specific member of their family (such as SARS-CoV, SARS-CoV-2, and MERS-CoV) even in a scenario of a reduced impact at the time of the related disease on humankind is still relevant as it could offer or inspire efficacious therapeutic strategies not only in the context of novel pathogenic mutations of the already known beta coronaviruses, but also when future zoonoses caused by other beta coronaviruses will emergence, which is not unlikely to occur in the current world where the interactions between humans and wildlife are made more and more frequent due to the growing loss of intact ecosystems worldwide.